Subliminal persuasion : influence & marketing secrets they don't want you to know - Lakhani, Dave, 1965- (John Wiley & Sons, 2008)
Every day you make purchasing decisions based on unconscious beliefs and biases you don't even know you have. Great marketers and persuaders know how to convince you to buy a product without your knowing it. The power of subliminal persuasion can move markets and control consumers. If you're an entrepreneur, salesperson, advertiser or business owner, understanding the art of subliminal persuasion will give your bottom line a big boost. Here, master marketer Lakhani reveals in detail the techniques people used to secretly persuade and influence you. He walks you through the Consumer Seduction Process and teaches you the latest techniques for leveraging the emotions, beliefs, and desires of your audience to move them in any direction you want--effectively, profitably, and even ethically.--From publisher description.